Anti-CD3 antibody ameliorates experimental autoimmune uveitis by inducing both IL-10 and TGF-β dependent regulatory T cells - Ke, Yan (Clinical immunology (Orlando, Fla.), 2011)
Copyright © 2010 Elsevier Inc. All rights reserved.